Innovative Theoretical Correlation of eπ With Mass, Number of Atoms and Enrichment Percentage (%E) Using Sayed’s Enrichment Formula - El-Mongy, Sayed (JOURNAL OF ADVANCES IN PHYSICS, 2022)
This article introduces an innovative theoretical correlation between eπ and enrichment percentage (%E) assay. Based on the published Sayed`s theorem and its applications, a simple equation was derived to calculate the %E. Different formulas for enrichment percentage calculation are also presented in this work. The theoretical calculations using the eπ formula show results with deviation from 0.96 to ~2.8%. A correlation between eπ, number of atoms (N), count rate (C), half life time (T1/2), efficiency (η) of the detector at specific energy, the branching ratio (Iγ), Avogadro`s number (AN), atomic weight (AW) and mass (M) was also found and elucidated. It can sharply state that this is first time to calculate the %E correlated with eπ by using what is called Sayed`s enrichment formula. The correlation of eπ and N AW AN M η Iγ T1/2 is a unique and pioneer scientific approach in the nuclear fields.